1996
DOI: 10.1074/jbc.271.40.24333
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+-dependent Lipid Binding Domain of P120GAP Mediates Protein-Protein Interactions with Ca2+-dependent Membrane-binding Proteinss

Abstract: The CaLB domain is a 43-amino acid sequence motif found in a number of functionally diverse signaling proteins including three Ras-specific GTPase activating proteins (GAPs). In the Ras GTPase activating protein, P120 GAP , this domain has the ability to confer membrane association in response to intracellular Ca 2؉ elevation. Here we have isolated three proteins, p55, p70, and p120, which interact with the P120 GAP CaLB domain in vitro. We identify p70 as the Ca 2؉-dependent phospholipid-binding protein annex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…Annexin A6 is found at the plasma membrane, in the endocytic compartment and in caveolae (Pol et al, 1999;Grewal et al, 2000;de Diego et al, 2002). Others and we have identified an interaction between annexin A6 and p120GAP (GAP) (Davis et al, 1996;Pons et al, 2001), but in addition, we showed that annexin A6 inhibited EGF-induced Ras/Raf-1 activity in CHO cells (Pons et al, 2001). Now we demonstrate that HDL-induced activation of Ras and Raf-1 is inhibited by annexin A6.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Annexin A6 is found at the plasma membrane, in the endocytic compartment and in caveolae (Pol et al, 1999;Grewal et al, 2000;de Diego et al, 2002). Others and we have identified an interaction between annexin A6 and p120GAP (GAP) (Davis et al, 1996;Pons et al, 2001), but in addition, we showed that annexin A6 inhibited EGF-induced Ras/Raf-1 activity in CHO cells (Pons et al, 2001). Now we demonstrate that HDL-induced activation of Ras and Raf-1 is inhibited by annexin A6.…”
Section: Introductionmentioning
confidence: 79%
“…Although a truncated form of the p120GAP C2 domain, the CaLB motif, binds to phospholipids in a Ca 2 þ -dependent manner (Gawler et al, 1995), experiments to demonstrate such an association with membranes and purified full-length p120GAP were unsuccessful (Clark et al, 1995). Data presented here suggest that annexin A6 is the Ca 2 þ -sensor to facilitate p120GAP membrane association in response to Ca 2 þ -elevation (Davis et al, 1996;Grewal et al, 2004).…”
Section: Egf-induced Ras Activation Is Elevated In Annexin A6-deficiementioning
confidence: 97%
“…For example, cPLA # has a CaLB domain, a feature in common with conventional forms of protein kinase C (PKC) and such PKCs are reported to be inhibited by annexin V [26] ; however, the molecular mechanism of this inhibition of PKC remains obscure. It is of interest that recently a direct interaction between P120 GAP and annexin VI has been reported involving this CaLB domain [27]. The fact that cPLA # also has a CaLB domain provides a possible mechanism for direct modulation of this PLA # by annexins.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 RACK1 is a scaffold for PKCα, which in earlier studies was shown to regulate p120GAP activity in T lymphocytes, 99 but also might target p120GAP to cholesterol-rich membrane domains, such as caveolae, in other settings. 100 By extending the previous work from Davis et al, 101 we demonstrated that AnxA6 binds to the CALB/C2 domain of p120GAP to facilitate the Ca 2+ -dependent recruitment of p120GAP to inactivate H-Ras at the plasma membrane upon EGFR activation. 30,39,40 For a more comprehensive description of the AnxA6/ p120GAP complex and its involvement in Ras inactivation upon EGFR activation, we refer the reader to previous reviews from our laboratories.…”
Section: Nf1mentioning
confidence: 99%